Respuesta :

Answer:

15. The numbers 3,-6, 12, -24,...

16. The numbers -3, -1,5, 23,...

17, The numbers 3, 9, 15, 21,...

18. [tex]\sum_{n=1}^{\infty} 4(\frac{1}{2})^{n-1}[/tex]

19. The sum is 8

20. [tex]a_{10}=-12[/tex]

Step-by-step explanation:

Question 15:

For the recursive sequence [tex]a_1=3, a_n=a_{n-1}*(-2)[/tex]

[tex]a_1=3,\\a_2=3(-2)=-6\\a_3=-6(-2)=12\\a_4=12(-2)=-24[/tex]

Therefore we get the numbers: 3, -6, 12, -24, ...

Question 16:

For the sequence [tex]a_n=3^{n-1}-4[/tex]

[tex]a_1=-3\\a_2=-1\\a_3=5\\a_4=23[/tex]

Therefore we have the numbers -3, -1, 5, 23, ....

Question 17.

For the recursive equation [tex]a_n=a_{n-1}+6[/tex]

[tex]a_1=3[/tex]

[tex]a_2=3+6=9[/tex]

[tex]a_3=9+6=15[/tex]

[tex]a_4=15+6=21[/tex]

The numbers generated are 3, 9, 15, 21,...

Question 18.

In the series [tex](4,2,1,\frac{1}{2},... )[/tex]

each following number is [tex]\frac{1}{2}[/tex] the previous number. The first term is 4, and the sequence has infinite terms; therefore, we have

[tex]\sum_{n=1}^{\infty} 4(\frac{1}{2})^{n-1}[/tex]

Question 19.

[tex]\sum_{n=1}^{\infty} 4(\frac{1}{2})^{n-1}=4*\sum_{n=1}^{\infty} (\frac{1}{2})^{n-1}[/tex]

since

[tex]\sum_{n=1}^{\infty} (\frac{1}{2})^{n-1}=1-\frac{1}{2^{n-1}}[/tex]

as n approaches infinity

[tex]\lim_{n \to \infty} 1-\frac{1}{2^{n-1}}=1[/tex]

therefore we have

[tex]\sum_{n=1}^{\infty} 4(\frac{1}{2})^{n-1}=4*\sum_{n=1}^{\infty} (\frac{1}{2})^{n-1}=4*1=4[/tex]

[tex]\boxed{\sum_{n=1}^{\infty} 4(\frac{1}{2})^{n-1}=4}[/tex]

The sum is 4.

Question 20.

an arithmetic sequence has the form

[tex]a_n=a_1+(n-1)d[/tex]

In our case [tex]a_1=6[/tex] and [tex]d=-2[/tex]; therefore we have

[tex]a_n=6-2(n-1)[/tex]

The 10th term of this sequence would be

[tex]a_{10}=6-2(10-1)=6-2(9)=-12[/tex]

[tex]\boxed{a_{10}=-12}[/tex]